Earth science - Tarbuck, Edward J.; Lutgens, Frederick K. (Pearson Education Limited, 2015)
For Introductory Earth Science Courses Ideal for undergraduates with little or no science background, Earth Science provides a student-friendly overview of our physical environment that offers balanced, up-to-date coverage of geology, oceanography, astronomy, and meteorology. The authors' texts have always been recognized for their readability, currency, dynamic art program, delivery of basic principles and instructor flexibility. This program will provide an interactive and engaging learning experience for your student